Relationship of Lifespan Physical Activity Engagement with Quality of Life in Community-Dwelling Adults: A Retrospective Study - De Moraes-Ferrari, G (John Wiley and Sons Inc, 2025)
Background and Aims: Lifelong physical activity (PA) engagement has been linked with several health benefits, such as the prevention of cardiovascular diseases. However, longitudinal studies investigating the association of lifelong PA with quality of life (QoL) needs to be more explored in literature. Methods: We analyze the association of lifelong PA engagement with quality of life (QoL) ini = 842 community-dwelling adults (56.5 ± 18.3 years, 61.7% of women). PA engagement during childhood and adolescence was retrospectively assessed considering supervised sports practice outside the school for at least 1 year. Current PA was assessed by Baecke score, and classified as highly active (4th quartile) and less active (1st–3rd quartile). QoL were assessed through by the SF-36, and classified as high (4th quartile) and low (1st–3rd quartile) QoL for each domain. Multiple logistic regression models (adjusted by sex, age, socioeconomic status, and disabling chronic conditions) analyzed the association between lifelong PA engagement with QoL. Results: Participants who engaged in PA in childhood and those currently classified into the highest quartile of Baecke score were more likely to present high QoL in isolated statistical models. Specific combinations of PA engagement in childhood + adolescence, childhood + adulthood, and adolescence + adulthood were associated with high physical functioning (OR: 3.34; 3.39; and 2.82), vitality (OR: 2.63; 2.08; and 2.40). Clustering life stages of PA engagement showed an incremental association for high physical functioning (2 stages OR: 2.49; 3 stages OR: 5.53), general health status (2 stages OR: 2.09; 3 stages OR: 2.79), and mental health (1 stage OR: 1.42; 3 stages OR: 2.79). Conclusion: Lifelong PA engagement is positively associated with QoL in adults. Actions for QoL promotion should focus on adherence of PA practice at all life stages, but this specific sample profile limited the generalization of results. © 2025 The Author(s). Health Science Reports published by Wiley Periodicals LLC.